Shifting the paradigm: Narratives of the future guide the development of Costa Rica's INDC - Veeger, Marieke; Vervoort, Joost M.; Martínez Barón, Deissy; León F. de; Paniagua F (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
This policy brief summarizes the process and main results of the development of Costa Rica´s INDC through a participatory process in which the building and use of future scenarios was the first step in a national dialogue to define, test and improve mitigation measures to lower emissions of greenhouse gases.